Temporal Sensitivity Changes with Extended Training in a Bisection Task in a Transgenic Rat Model - Brown, Bruce L.; Höhn, Sophie; Faure, Alexis; von Hörsten, Stephan; Le Blanc, Pascale; Desvignes, Nathalie; El Massioui, Nicole; Doyere, Valerie (Frontiers in Integrative Neuroscience, 2011)
The present study investigated temporal perception in a Huntington Disease transgenic rat model using a temporal bisection procedure. After initial discrimination training in which animals learned to press one lever after a 2-s tone duration, and the other lever after a 8-s tone duration for food reward, the bisection procedure was implemented in which intermediate durations with no available reinforcement were interspersed with trials with the anchor durations. Bisection tests were repeated in a longitudinal design from 4 to 8 months of age. The results showed that response latencies evolved from a monotonic step-function to an inverted U-shaped function with repeated testing, a precursor of nonresponding on trials with intermediate durations. We inferred that temporal sensitivity and incentive motivation combined to control the transformation of the bisection task from a two-choice task at the outset of testing to a three-choice task with repeated testing. Changes in the structure of the task and/or continued training were accompanied by improvement in temporal sensitivity. In sum, the present data highlight the possible joint roles of temporal and non-temporal factors in the temporal bisection task, and suggested that non-temporal factors may compensate for deficits in temporal processing.